THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL SELF EFFICACY ON PERSONAL FINANCIAL MANAGEMENT OF UT UPBJJ PONTIANAK STUDENTS - Arif Miftahudin; Lenny Menara Sari Saragih (RADJA PUBLIKA, 2025)
Lack of financial literacy is one of the factors involved in financial decisions, where the lack of information can have a negative impact. Self-Efficacy or self-confidence about financial capabilities affects a person's financial behavior, namely it can help in implementing and following up on a change in a person's financial behavior for the better. The study aims to understand, know and explore financial literacy, financial self-efficacy, and personal financial management of UT UPBJJ Pontianak students. The study is a quantitative study with a multiple regression method. The population in this study were all UT Management Department S1 UPBJJ Pontianak students with a sampling technique using the Cochran formula method of 100 samples. This study concludes that financial literacy and financial self-efficacy each have a positive direction with the personal financial management variable. Financial literacy and financial self-efficacy have a partial and simultaneous significant effect on the personal financial management of Management study program students at UPBJJ Pontianak. Financial literacy and financial self-efficacy affect the personal financial management variable of students by 86% and the rest is influenced by other variables outside this study.There are still other variables that influence personal financial management, so researchers hope that further researchers will perfect this research by adding other variables outside of this research.